Kontroversi Pemikiran Teks Keagamaan Kiai Abdul Mu'thi, Pondok Pesantren An-Najah, Magelang - Dandung Budi Yuwono (LP2M UIN Sunan Kalijaga, 2017)
This article discusses the thoughts of Kiai Mu'thi religious texts that have sparked controversy and internal conflicts among the NU as a critical discourse. Data collection is done by interview, observation, and documentation. The result of the research indicates that the problem of 73 classes (firqah) is a material that is never left behind in every Kiai Mu'thi recitation, as well as a commitment to always remind to fellow Muslims, especially the nahdliyin group which he calls the alignment of aqidah and amar ma'ruf nahi munkar. Da'wah movement is more oriented towards kiai, ulama, religious leaders, and religious teachers so that they can return in the direction that has been considered heretical. Kiai Mu'thi da'wah movement is a deconstruction as well as a reconstruction of discourse construction that develops among nahdliyin, and which is also a representation of the outward effort of the dominant pesantren hegemony in its territory in order to form entities and social relations.